Lungworm infections in harbour porpoises (Phocoena phocoena) in the German Wadden Sea between 2006 and 2018, and serodiagnostic tests. (April 2021) - Reckendorf, Anja; Everaarts, Eligius; Bunskoek, Paulien; Haulena, Martin; Springer, Andrea; Lehnert, Kristina; Lakemeyer, Jan; Siebert, Ursula; Strube, Christina
Abstract: Pseudaliid lungworm (Metastrongyloidea) infections and associated secondary bacterial infections may severely affect the health status of harbour porpoises ( Phocoena phocoena ) in German waters. The presented retrospective analysis including data from 259 harbour porpoises stranded between 2006 and 2018 on the German federal state of Schleswig-Holstein's North Sea coast showed that 118 (46%) of these stranded individuals harboured a lungworm infection. During this 13-year period, a significant difference in annual lungworm prevalence was only observed between the years 2006 and 2016. Lungworm coinfections of bronchi and pulmonary blood vessels were observed in 85.6% of positive cases. Mild infection levels were detected in 22.9% of infected animals and were most common in the age class of immature individuals (74.1%). Moderate and severe infections were present in 38.1% and 39.0% of the lungworm positive animals, respectively. Their distribution in immatures (51.1% and 54.3%) and adults (48.9% and 43.4%) did not show significant differences. In stranded animals, lungworm diagnosis can be easily obtained via necropsy, while reliable lungworm diagnosis in living porpoises requires invasive bronchoscopy or faecal examination, which is difficult to obtain in cetaceans. To overcome this issue, an enzyme-linked immunosorbent assay (ELISA) and immunoblot based on recombinant major sperm protein (MSP) of the cattle lungworm were evaluated as potential diagnostic tools in harbour porpoises. However, in contrast to hitherto other investigated host species, no reliable antibody response pattern was detectable in harbour porpoise serum/plasma or whole blood samples. Thus, MSP-based serological tests are considered unsuitable for lungworm diagnosis in harbour porpoises. Graphical abstract: Image 1 Highlights: Overall lungworm prevalence in North Sea harbour porpoises was 46%. Co-infection of bronchial tree and pulmonary vessels in 85.5% of positive animals. Most harbour porpoises suffered from moderate (38%) or severe infection (39%). Both MSP-ELISA and immunoblot did not reveal reliable results.